How Does Financial Risk Management Impact Financial Performance of Microfinance Banks? - Abdulrauf, Lukman Adebayo-Oke; Rabiu, Sherifdeen Adebola; Akande, Joseph Olorunfemi; Gbadebo, Adedeji Daniel (Acta Universitatis Danubius. Œconomica, 2024)
Microfinance banks (MFBs) in Nigeria play an important role of delivering financial services to the underserved population and low-income individuals. MFBs are exposed to various financial risks, including borrower defaults and liquidity management, posing serious survival threats. We apply the autoregressive distributive lag (ARDL) regression, on published data from 1993 to 2022, to confirm how financial risk management of the MFBs in Nigeria impacts their financial performance. The finding from the short run of the main (ROA) estimation identifies that except for the loan-deposit magnitude, which is insignificant, the coefficients on capital adequacy strength, risk asset quality, liquidity strength and loan loss provision are significant. For the long run, capital adequacy, liquidity, risk asset quality and loan loss provision have significant coefficient while loan-deposit magnitude has an insignificant coefficient. The lag term of error correction is negative (-1.60) and significant, implying that the model would converge to equilibrium upon any perturbation. Similar results are evident when the return on equity is considered as a measure of financial performance to verify the sensitivity of the outcomes. This suggests the estimation is not sensitive to any performance measure used. The findings underscore the importance of capital adequacy and liquidity strength for improving the financial performance as well as the detrimental impact of risk asset quality and high loan loss provisions on the MFBs. To ensure enhanced financial performance, sustainability and effectiveness, we recommend offer that policy markets should different regulatory measures including recapitalization, reshaping of risk asset holdings, regulating loan loss provisions, clarifying regulations on loan-deposit ratios, and regulating liquidity levels.